Societal Derivations for the Illegal Gun Trafficking: In Addis Ababa: Ethiopia - Birara, Desalegn (International Journal of Criminology and Sociology, 2017)
Gun is not allowed to buy and own for civilians in Ethiopia. There are national laws, regulations and administrative procedures that allow production, export, import, transit or retransfer of small arms which are limited to state and federal security purposes; while any other, if any, is explained by the anti-terrorists act. The law requires a record of the acquisition, possession and transfer of each privately held firearm be retained in an official register. Nonetheless, both the anti-terrorist act and other firearm regulations, have not been successfully implemented to prevent illicit trafficking of guns and violent crimes associated with illegal gun possession. Peripheral neighborhoods in Addis Ababa prove its existence and people in these neighborhoods are found to be defenseless. Graveyards of church and jungles have been the busiest illegal gun exchange belts. The number of people involved in the different courses of action to procure guns is also considerable. This research assesses the societal apprehension to the illicit gun exchange. Residents in the village where illegal gun trafficking took place have negative impressions to it. The illegal gun exchange created fear in the residents; limited the right of people to movement; and embarrassed in many respects. Trust on police for security purposes is diminishing; because, residents understood policemen, themselves, as part of the illicit trafficking. The midnight time when people are most likely to sleep is the peak time of the gunfire. This compels to prognosticate the impending terrorism; as its opportunity of emergence and development is open.